(untitled) (Research, Society and Development, 2020)
Introduction: Social Anxiety Disorder characterized as accentuated fear from situations of exposure to collective judgment, currently occupies the 3rd place in the ranking of the main psychological problems in the contemporary world. Objective: to investigate the epidemiological profile of students with traits of Social Anxiety Disorder. Method and Materials: this is a quantitative epidemiological, observational, analytical cross-sectional study. Held at the School Clinic of Faculdade Estácio de Alagoas - Estácio FAL. The study had as inclusion criteria students enrolled between the 1st and 2nd periods of several courses. In which a questionnaire divided into two sections was applied: the first section corresponds to sociodemographic characteristics; and the second section addresses issues related to social anxiety disorder. Results: 69 participants were selected to constitute the sample. In which, it was identified that the social situations that cause the most discomfort to participants are “speaking in public (presenting papers, giving lectures, etc.)” with 76.8%, consecutively, “asking questions with teachers in the classroom” with 15.9% and “interacting with unfamiliar people, strangers” 10.1%. Discussion: in the face of studies, TAS strongly affects the psychological health of students, making it impossible for them to carry out their activities successfully. Conclusion: this study clearly shows the data and profile of these students, being necessary a more in-depth study using other instruments for a large-scale investigation, as well as the sample must be expanded due to the extension of the study.